2002
DOI: 10.1128/mcb.22.7.2204-2219.2002
|View full text |Cite
|
Sign up to set email alerts
|

ErbB2/Neu-Induced, Cyclin D1-Dependent Transformation Is Accelerated in p27-Haploinsufficient Mammary Epithelial Cells but Impaired in p27-Null Cells

Abstract: ErbB2/Neu destabilizes the cyclin-dependent kinase (Cdk) inhibitor p27 and increases expression of cyclin D1. Therefore, we studied the roles of p27 and cyclin D1 in ErbB2-mediated mammary epithelial cell transformation. Overexpression of ErbB2 or cyclin D1 in p27 ؉/؊ primary murine mammary epithelial cells resulted in increased proliferation, cyclin D1 nuclear localization, and colony formation in soft agar compared to those in p27 ؉/؉ cells. In contrast, ErbB2-or cyclin D1-overexpressing p27 ؊/؊ cells displa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
82
2
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(93 citation statements)
references
References 64 publications
7
82
2
2
Order By: Relevance
“…Interestingly, our results appear in contrast with those previously published regarding the p27-null mice carrying the ErbB2/Neu oncogene (MMTVneu/p27 K/K ; Muraoka et al 2002). The mammary glands of these mice showed decreased proliferation, as well as markedly prolonged tumor latency, compared with MMTV-neu/p27 C/C glands.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Interestingly, our results appear in contrast with those previously published regarding the p27-null mice carrying the ErbB2/Neu oncogene (MMTVneu/p27 K/K ; Muraoka et al 2002). The mammary glands of these mice showed decreased proliferation, as well as markedly prolonged tumor latency, compared with MMTV-neu/p27 C/C glands.…”
Section: Discussioncontrasting
confidence: 99%
“…The mammary glands of these mice showed decreased proliferation, as well as markedly prolonged tumor latency, compared with MMTV-neu/p27 C/C glands. Conversely, the TRK-T1/p27-null mice showed a great similarity with the MMTV-neu/p27 C/K mice, whose mammary glands exhibited alveolar hyperplasia, enhanced proliferation, decreased apoptosis, and accelerated tumor formation compared with MMTVneu/p27 C/C mammary glands (Muraoka et al 2002). It is likely that in MMTV-neu/p27 K/K mice, the complete absence of the p27 protein leads to an impairment of cyclin D1/Cdk4 function, that makes these mice more resistant to transformation.…”
Section: Discussionmentioning
confidence: 95%
“…Compared to a complete absence of p27 protein due to loss of heterozygosity, low levels of p27 may be more favorable to transformed cells by allowing the assembly of complexes between D-type cyclins and cdk4 and cdk6, without inhibiting cdk2 complexes. This hypothesis is supported by a mouse model showing that p27 +/− mammary epithelium is more susceptible to oncogene-induced tumorigenesis than p27 −/− mammary glands at least in cooperation with particular oncogenes [36] (see also previous section).…”
Section: P27 and Human Cancersmentioning
confidence: 62%
“…Furthermore, concomitant inactivation of one allele of the tumor suppressor gene Pten and both or even one of the Cdkn1b alleles accelerates spontaneous neoplastic transformation and incidence of tumors of various histological origins [35]. The fact that p27 is a haploinsufficient tumor suppressor is also shown by a recently described mouse model in which the expression of the Erb2 oncogene in p27 −/− mammary epithelium induced breast tumors with decreased cdk4 activity and markedly prolonged tumor latency, compared to MMTV-Erb2/p27 +/− glands [36]. Indeed, this mouse model suggests that loss of just one allele might provide a growth advantage superior to the loss of both alleles, at least in some tissues and in cooperation with certain oncogenes (see following section).…”
Section: P27 As a Tumor Suppressor In Mouse Modelsmentioning
confidence: 93%
“…The idea that p27 might have activities which are beneficial for the tumor cell is not entirely new. For example in an ErbB2 dependent mouse breast cancer model, Muraoka and co-workers showed that while loss of one p27 allele accelerated breast cancer development loss of both alleles decreased cyclin D dependent kinase activity which correlated with an increased tumor latency [5]. Since the p27 CKˉ mutant is not able to bind cyclin/cdk complexes an influence on the formation of cyclin D containing complexes can be excluded as a primary cause for the tumor phenotype.…”
mentioning
confidence: 99%